Analysis of water quality in mangrove areas around vanname shrimp ponds in Pesisir Selatan Regency, West Sumatra - Kamal, Eni; Lubis, Amelia Sriwahyuni; Yuspardianto, Yuspardianto; Bukhari, Bukhari; Desmiati, Ira (Universitas Malikussaleh, 2025)
This research aims to analyze the condition of the mangrove ecosystem due to the activities of Vaname shrimp ponds in the Tarusan area, Pesisir Selatan, West Sumatra. This research was conducted in Tarusan, Pesisir Selatan Regency, West Sumatra. The sampling location points are three stations. The method used is survey and field observation. Physical sampling procedures using water quality tools. Chemical sampling is carried out using a sterile sample bottle and then filled completely with water. The data analysis used in this research is descriptive data analysis, which is a data analysis technique for analyzing data by creating pictures or tables from the results of the data that has been collected. Based on this data, there are indications of significant water pollution in the mangrove areas adjacent to vaname shrimp ponds, mainly caused by high concentrations of organic matter, copper, lead and zinc.Keywords: Mangroves; Shrimp; Vanname; Water Quality